2014
DOI: 10.1007/s40429-014-0033-8
|View full text |Cite
|
Sign up to set email alerts
|

Translating Neurobiology to the Treatment of Dual Diagnosis: The Example of Nicotinic Receptors and Neurocognitive Endophenotypes in Schizophrenia

Abstract: Endophenotypes are heritable traits associated with psychiatric illness. Certain endophenotypes associated with schizophrenia such as working memory and sensory gating may be linked to the high tobacco smoking prevalence in patients with schizophrenia. Evidence suggests a critical role for the nicotinic acetylcholine receptor system (nAChR) in the underlying pathophysiology of schizophrenia. Despite the negative consequences associated with tobacco use, patients with schizophrenia have a much more difficult ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…In this line, sensory gating deficits in schizophrenia are associated with genes related to the nicotinic cholinergic receptors ( Bridgman et al, 2014 , De Luca et al, 2004 , Freedman et al, 2008 , Leonard et al, 2007 , Petrovsky et al, 2013a ), particularly, to the receptor alpha 7 subunit (CHRNA7; De Luca et al, 2004 , Leonard et al, 2007 ). Another recent study showed that a single nucleotide polymorphism (SNP) in the alpha 7 subunit gene correlated with both the diagnosis of schizophrenia and impaired performance in visual backward masking (VBM; Bakanidze et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this line, sensory gating deficits in schizophrenia are associated with genes related to the nicotinic cholinergic receptors ( Bridgman et al, 2014 , De Luca et al, 2004 , Freedman et al, 2008 , Leonard et al, 2007 , Petrovsky et al, 2013a ), particularly, to the receptor alpha 7 subunit (CHRNA7; De Luca et al, 2004 , Leonard et al, 2007 ). Another recent study showed that a single nucleotide polymorphism (SNP) in the alpha 7 subunit gene correlated with both the diagnosis of schizophrenia and impaired performance in visual backward masking (VBM; Bakanidze et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%